MEKANISME JASA KUPON PERAWATAN BERKALA DALAM MENINGKATKAN KEPUASAN PELANGGAN TUNAS DWIPA MATRA, MUARA SABAK BARAT: KAJIAN DALAM PERSPEKTIF ISLAM - Aulia, Noerfirdha; Arif Musthofa, M.; Kuswanto; Wandi (Jurnal Dinamika Ekonomi Syariah, 2025)
Tunas Dwipa Matra continues to innovate to improve competitiveness and customer satisfaction through the implementation of effective strategies. One of the strategic steps introduced is the Periodic Maintenance Coupon (KPB) program. KPB is an exclusive service in the form of service claims aimed at new motorcycle buyers as a form of appreciation and an effort to maintain long-term relationships with customers. In this program, new motorcycle buyers get facilities in the form of four periodic maintenance services as part of the vehicle purchase package. In the implementation of the first KPB, customers receive benefits in the form of free service accompanied by the provision of engine oil at no additional cost. This provides a double benefit, namely optimal engine maintenance as well as reduced maintenance costs for customers. Meanwhile, in the second, third, and fourth KPBs, customers are still entitled to free service even without additional engine oil. Thus, this program not only helps customers in maintaining their vehicles in prime condition but also encourages them to carry out routine maintenance. This KPB program is designed with a clear goal, namely to provide added value to customers and build their loyalty to Tunas Dwipa Matra products and services. By providing consistent and useful services, the company hopes to create a mutually beneficial relationship between the company and customers, while improving the brand image in the eyes of consumers. This strategy is expected to strengthen Tunas Dwipa Matra’s position as one of the best automotive service providers in the market.